Key elements for the future of technology sourcing in the Peruvian industry: a prospective study - Cabrera, Rony (2019)
This article explore the future of technology sourcing in the Peruvian industry until 2030 in order to determine key elements to strategic formulation. Based on tool of prospective, we found the following axes of uncertainty that matter in the future of Peruvian technology sourcing: technological innovation, market dynamism and skilled people in R&D. Finally, and ideal scenario is described and present a discussion of the results and conclusions with limitations and futures directions.